2004
DOI: 10.1111/j.1526-0968.2004.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Filtration Leukocytapheresis Therapy in the Treatment of Rheumatoid Arthritis Patients Resistant To or Failed with Methotrexate

Abstract: Filtration leukocytapheresis (LCP) is a treatment for abnormal autoimmune states, which removes responsible leukocytes from the peripheral blood. To examine the efficacy of LCP therapy in the treatment of rheumatoid arthritis (RA), nine patients were selected, who were either resistant to methotrexate, or failed with methotrexate due to drug ineffectiveness or adverse side effects. For these patients, LCP therapy was performed once a week for five weeks. After five LCP treatments, the patients were observed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 15 publications
1
27
0
2
Order By: Relevance
“…Depleting excess and activated leukocytes by intensive LCAP treatment may alleviate inflammation and promote the remission of AOSD. The LCAP treatment corrected the Th1/Th2 cytokine balance in the patients with RA (15,21). Maternal tolerance toward fetal alloantigens is explained by predominant Th2-type immunity during pregnancy.…”
Section: Discussionmentioning
confidence: 96%
“…Depleting excess and activated leukocytes by intensive LCAP treatment may alleviate inflammation and promote the remission of AOSD. The LCAP treatment corrected the Th1/Th2 cytokine balance in the patients with RA (15,21). Maternal tolerance toward fetal alloantigens is explained by predominant Th2-type immunity during pregnancy.…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3] No major adverse effects have been observed so far. Kempe et al 3 reported that improvements in symptoms appeared slowly, but persisted until 12 weeks after the LCAP therapy. A slow response was also observed in our case.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the LCAP therapy has been reported in the past decade. [1][2][3] Therefore, LCAP is sometimes indicated for RA in Japan. Herein, we report a case of effective treatment of LCAP in an acquired IFM-resistant patient with RA whose response to IFM was recovered after LCAP.…”
Section: Introductionmentioning
confidence: 99%
“…DMARD'lar ya da biyolojik ajanlara iyi yanıt vermeyen RA'li hastalarda etkili olduğu bildirilmiştir 18 . Vücut ağırlığı başına daha yüksek bir kan hacmi (100 ml/kg) işleyebilen A kolonu (CS-180S) veya 60 ml/kg kanı işleyebilen konvansiyonel kolonu (CS-100) son zamanlarda geliştirilmiştir.…”
Section: Terapotik Aferezin Etki Mekanizmasıunclassified